Mineralogy of Recent Sediments of AL-Teeb River Basin East Missan Governorate Southeastern Iraq - Kadhim, Ali H.; Ali, Maysoon O. (Iraqi Journal of Science, 2022)
The main aim of this research is to define the mineralogical composition of recent sediments deposited around the Al-Teeb river basin in eastern Missan, trying to determine the provenance or the source of these sediments.       The study area represents the southeastern edge of the Mesopotamian Plain and is part of it. Quaternary deposits cover most of the area. It is clayey with old sea and river deposits and part of aeolian deposits.       These sediments cover 95% of the study area, while the older rocks, which date back to the Tertiary (Late Miocene – Pliocene), exposed in the area east and northeast of the Al-Teeb area, made up hills which back to the undifferentiated Pliocene Mukdadiya and Bai-Hassan formations.       The light components of these sediments consist mainly of quartz, feldspars (potash and plagioclase feldspar), sedimentary rock fragments (carbonate rock fragments, chert rock fragments, evaporates fragments), igneous rock fragments, and metamorphic rock fragments      The heaviest minerals are opaque, amphiboles, pyroxenes, chlorite, epidotes, biotite, garnet, muscovite, zircon, kyanite, staurolite, and rutile.     These sediments are typically formed by sedimentary rocks (single or many cycles), low and high-rank metamorphic rocks, acidic and basic igneous rocks, and pegmatite rocks.     The high percentage of opaque heavy minerals in clastic sediment refers to unstable clastic sediments. The stability issue to the areas during the study shows that there are significant variances over the several places, indicating dissimilar sources and types of source rocks